Caminhos da vertigem: rupturas do eu no happening PanAmérica - Carlotti, Tatiana Cristina (2014)
The present dissertation aims to analyze the narrator/character disembodiment and the body presence in the narrative construction in José Agrippino de Paula s PanAmérica. The body into which the subject inserts himself acquires an enormous proportion throughout the work: the body of anonymous heroes, hundreds of them fragmented, creased and dulled in the asphyxiating tubes of the cultural machine; the individualized body, the source of pleasure, beauty, warmth and proximity; the narrative body converted into happening by the operative movement of the chaotic writing strengths. It is in this vertiginous and raving context that the narrator tries to restate his own existence towards the illogicalness of a world and also of a narrative laid in ruins. In our walk through the work, whose explosives are switched on at each scenic unity, we have attempted to ascertain how the narrator and the characters disembodiment along the work and the construction of a strongly erotic narrative were used to build a sensory happening, determined to constitute a possible anthropophagic answer to the ideological dichotomies which marked the 1960s in Brazil